Semiotika Rambu-Rambu Lalu Lintas Laut - Surnata Surnata; Hayatun Nufus; Kodrat Alam; Elfita Agustini (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Traffic signs are part of road equipment that contains symbols, letters, numbers, as well as sentences and combinations in them and serves to provide warnings, prohibitions, orders, and instructions for road users. The color and shape of a traffic sign contain meanings that are not understood by everyone. The problem in this study is "How is the semiotics of traffic signs in the lateral flare buoy system and cardinal beacon buoy?" This study aims to identify and describe the lateral and cardinal flare buoy systems. The method used by the author in this study is a qualitative method. The results of the color research on the cardinal and lateral buoys show the function and position of the buoy, such as the color on the pole which is yellow on the bottom and black on the bottom or the placement of various colors. The green and red colors on the lateral buoy indicate the position of the sign such as the left or the starboard position of the ship. Likewise with the lateral cardinal shape, if it is pointed at the top, it means that the buoy is on the right, if the lateral buoy is blunt, it means that the buoy is on the left. The colors found on the cardinal and lateral buoys indicate the function and position of the buoy, such as the color on the pole which is yellow on the bottom and black on the bottom or the placement of various colors. The green and red colors on the lateral buoy indicate the position of the sign such as the left or the starboard position of the ship. Likewise with the lateral cardinal shape, if it is pointed at the top, it means that the buoy is on the right, if the lateral buoy is blunt, it means that the buoy is on the left.